2017
DOI: 10.1001/jama.2016.21043
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Treatment and Coronary Artery Plaque Volume in Older Men With Low Testosterone

Abstract: IMPORTANCERecent studies have yielded conflicting results as to whether testosterone treatment increases cardiovascular risk.OBJECTIVE To test the hypothesis that testosterone treatment of older men with low testosterone slows progression of noncalcified coronary artery plaque volume.DESIGN, SETTING, AND PARTICIPANTS Double-blinded, placebo-controlled trial at 9 academic medical centers in the United States. The participants were 170 of 788 men aged 65 years or older with an average of 2 serum testosterone lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
213
0
2

Year Published

2017
2017
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(223 citation statements)
references
References 33 publications
3
213
0
2
Order By: Relevance
“…The Cardiovascular sub‐study of T‐Trials reported a greater increase in non‐calcified coronary plaque volume in men following one year of T treatment compared to placebo . At baseline, 50% of these men had severe atherosclerosis, emphasizing that the highly specific selection of men with low circulating T produced a cohort with high rates of established atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Cardiovascular sub‐study of T‐Trials reported a greater increase in non‐calcified coronary plaque volume in men following one year of T treatment compared to placebo . At baseline, 50% of these men had severe atherosclerosis, emphasizing that the highly specific selection of men with low circulating T produced a cohort with high rates of established atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the cardiovascular trial, the researchers found that the volume of arterial plaque increased significantly more in the testosterone-treated group compared to the untreated control group. 52 For the cognition trial, after a year of treatment, there was no significant change in verbal memory, visual memory, or problem solving. 53 In a pilot clinical trial in humans with MS, 10 male MS patients aged <65 years were treated with 10 g of gel containing 100 mg of testosterone in a cross-over design (6-month observation period followed by 12 months of treatment).…”
Section: Testosterone As a Therapymentioning
confidence: 94%
“…Recently meta‐analyses have reported the positive impact of T therapy on insulin resistance and glycaemic control in men with diabetes and metabolic disease (Figure 3) . Six well‐conducted studies have evaluated patients properly diagnosed and treated to target levels for sufficient duration …”
Section: Low Testosterone a Risk Factor Or Risk Marker—the Clinical mentioning
confidence: 99%
“…Sharma et al retrospectively evaluated 83 010 male veterans with documented low TT levels. The subjects were categorised into 3 groups: T therapy with resulting normalisation of TT levels (group 1), defined as the lower limit of the laboratory reference range; T therapy without normalisation of TT levels (group 2); and did not receive T therapy (group 3).…”
Section: Low Testosterone a Risk Factor Or Risk Marker—the Clinical mentioning
confidence: 99%